2018
DOI: 10.3390/su10103718
|View full text |Cite
|
Sign up to set email alerts
|

Citrus and Winery Wastes: Promising Dietary Supplements for Sustainable Ruminant Animal Nutrition, Health, Production, and Meat Quality

Abstract: Citrus and grapes are the most widely grown fruits globally, with one-third of total production used for juice and wine making. The juice and winemaking processes generate large quantities of solid organic wastes including citrus pulp and grape pomace. These fruit wastes pose serious economic, environmental, and social challenges, especially in low-to-middle-income countries due to financial, technological, and infrastructural limitations. They are, however, rich in valuable compounds which can be utilized in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 90 publications
2
20
0
1
Order By: Relevance
“…Anthocyanin may decrease DMI because its astringent property, negatively effecting on the growth performance of ruminants [21]. Our ndings indicated that the consumption of PCP did not side effect on DMI and growth performance in goats, suggesting that anthocyanin had no side effects on production performance.…”
Section: Discussionmentioning
confidence: 57%
“…Anthocyanin may decrease DMI because its astringent property, negatively effecting on the growth performance of ruminants [21]. Our ndings indicated that the consumption of PCP did not side effect on DMI and growth performance in goats, suggesting that anthocyanin had no side effects on production performance.…”
Section: Discussionmentioning
confidence: 57%
“…Cattle on rangelands or custom feedlots can be supplemented with novel and alternative feeds, including locally available plant residues and by-products (PBP) from agro-industrial processes [62][63][64]. Compared to grazing exotic cattle breeds, indigenous breeds are a significant source of anthropogenic greenhouse gas emissions (i.e., CH 4 and NO 2 ) because of their low performance based on beef and milk yield traits [65,66].…”
Section: Cattle Feeding Strategiesmentioning
confidence: 99%
“…Grape pomace in particular, is a by-product of wine production which has been the subject of several dedicated reviews that explored its potential as a source of antimicrobial agents [ 27 ], human health promoter [ 28 ] and animal nutrition [ 29 ] in part due to its high PACs content.…”
Section: Introductionmentioning
confidence: 99%